A method for processing high-strength ceramic insulator
By optimizing the blank and glaze process of ceramic insulators, adding diatomaceous earth and silicon powder, and ozone treatment during the glazing process, the problems of insufficient strength and short service life of ceramic insulators are solved, and the high strength and long life of ceramic insulators are achieved.
Patent Information
- Application Number
- CN202411836069.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
When faced with high mechanical stress and electrical load, existing ceramic insulators have insufficient strength and short service life, making it difficult to meet the safe operation needs of high-voltage lines.
By optimizing the blank and glaze process of ceramic insulators, adding diatomaceous earth and silicon powder to improve thermal and mechanical properties, and ozone treatment of the surface of the blank during the glaze process, a glass-like film is generated to improve the bonding strength between the glaze and the blank.
It significantly improves the overall strength and service life of ceramic insulators, and meets the safe operation needs of high-voltage lines.
Smart Images

Figure CN119320265B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic insulator production, in particular to a high-strength ceramic insulator processing method. Background Art
[0002] Insulators are devices installed between conductors at different potentials or between conductors and grounded structures, which can withstand voltage and mechanical stress. There are many types of insulators with different shapes. Although the structures and appearances of different types of insulators are quite different, they are all composed of two major parts: insulating parts and connecting fittings. Insulators are a special type of insulating control component that can play an important role in overhead transmission lines. In the early years, insulators were mostly used on electric poles, and gradually developed into high-type high-voltage electric wire connection towers with many disc-shaped insulators hung at one end. It is to increase the creepage distance and is usually made of glass or ceramic, which is called an insulator. Insulators should not fail due to various electromechanical stresses caused by changes in environmental and electrical load conditions, otherwise the insulators will not have a significant effect and will damage the use and service life of the entire line.
[0003] The patent with the authorization announcement number CN113968726A discloses a method for preparing a high-strength alumina suspension insulator and a porcelain insulator structure, comprising the following steps: Step 1: using the following mass percentages of blank raw materials, including 20-30% industrial alumina, 15-25% feldspar, 20-25% ball clay, 20-25% clay granules and SrCO3 3-5%, wherein the particle size of the clay granules is 20-40 meshes; step 2: sand grinding the blank raw material to obtain blank particles with a diameter of 3-5 microns; step 3: ball milling, impurity removal, moisture control, drying, blanking, drying, glazing, and sintering the blank particles obtained in step 2 in sequence to obtain an alumina porcelain insulator body; step 4: the alumina porcelain insulator body is made into a structure with a rounded rectangular outer contour and an arch-shaped inner contour in the longitudinal section as a porcelain head, and the porcelain head is assembled with a steel foot to obtain a porcelain insulator structure; the prepared porcelain insulator has the advantages of high production qualification rate, stable mechanical properties, stable electrical properties, etc., and meets the safe operation requirements of high-voltage lines; however, the patent technical solution does not involve process improvements for the surface glaze of ceramic insulators. In the structural improvement and design of ceramic insulators, process improvements for the surface glaze of ceramic insulators are very important for improving the overall strength and service life of the insulators.
[0004] Insulators play a very important role in power transmission lines, so insulators have very high quality requirements, and their mechanical, electrical and thermal performance requirements are very high. In view of the development needs of power-related fields, the performance of existing insulators has become increasingly difficult to show high applicability, so it is necessary to design and produce new high-strength insulators for high-requirement fields.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] In view of the problems raised in the above background technology, the purpose of the present invention is to provide a high-strength ceramic insulator processing method, which optimizes the relevant blank process and glaze process in the ceramic insulator production process to meet the higher demands of industry development.
[0007] In order to achieve the above object, in the technical solution of the present invention, a high-strength ceramic insulator processing method is provided, which specifically comprises the following steps:
[0008] S1-1, the following mass percentages of blank raw materials are used: kaolin ,diatomite , potassium feldspar , bentonite , Quartzite , Silicon powder It should be noted that, as a raw material for the blank, diatomaceous earth has excellent thermal insulation properties. Adding diatomaceous earth can improve the thermal properties of ceramics. Silicon powder, as an additive in the blank, has excellent thermal and mechanical properties, which can improve the performance of ceramics and reduce the porosity of the ceramic blank.
[0009] S1-2, the raw materials of the blank obtained in step S1-1 are sand-milled and sieved with a 200-mesh sieve respectively, and after mixing, they are wet-milled, granulated, aged, and pressed into shape, and dried to obtain a blank; mainly by drying at room temperature or low temperature, and the moisture content of the blank after drying is less than .
[0010] S2-1, using the following mass percentage of glaze raw materials, diatomaceous earth , pyrophyllite , Kaolin ,talc , Borax , Quartzite It should be noted that, as a glaze raw material, pyrophyllite has a small and linear expansion coefficient, good thermal stability and very small wet expansion, which can improve the stability of the glaze.
[0011] S2-2, the diatomite obtained in step S2-1 is sand-ground through a 120-mesh sieve, and other glaze raw materials are sand-ground through a 550-mesh sieve respectively, so that other glaze raw materials can fill the surface mesopores of the diatomite.
[0012] S2-3, adding a saturated boric acid solution to the diatomaceous earth obtained in step S2-2 to obtain a mixed liquid, wherein the volume ratio of the diatomaceous earth to the saturated boric acid solution is , heating the mixed liquid to acid-leach the diatomaceous earth to obtain an intermediate liquid.
[0013] S2-4, filtering the intermediate liquid obtained in step S2-3 and heating it to obtain a dry solid.
[0014] S2-5, the dry solid obtained in step S2-4 is sand-milled again through a 120-mesh sieve, and mixed with other glaze raw materials obtained in step S2-2 to obtain a mixed glaze and calcined until the specific gravity of the mixed glaze raw material is .
[0015] S2-6, wet-milling the mixed glaze obtained in step S2-5 to obtain glaze slurry.
[0016] S3-1, glazing the green body obtained in step 1-2 and firing it to obtain a finished product, wherein the surface of the green body is subjected to ozone treatment during glazing.
[0017] Further, in the technical solution of the present invention, in the process of step S2-3, the acid leaching process is to heat to , insulation The weak acidity of boric acid can remove the soluble impurities in the diatomite. Inorganic impurities have low solubility and therefore most of them are retained.
[0018] Further, in the technical solution of the present invention, in the process of step S2-4, the heating and drying process is to heat to , insulation After filtering, part of the saturated boric acid solution remains in the intermediate liquid, and the saturated boric acid solution undergoes thermal decomposition reaction during the drying process to generate boron oxide.
[0019] Further, in the technical solution of the present invention, during the step S2-5, the calcination temperature is Calcination time is , and stirring is performed during calcination. High-temperature calcination can increase the mesopore volume of diatomite, and mixing and stirring can cause the blank raw material particles to fill the surface mesopores of diatomite.
[0020] Furthermore, in the technical solution of the present invention, in the step S3-1, the sintering process of the green body is The firing time is , the ozone treatment time is The surface of the green body is modified by treating the green body with ozone to make the hydrophilic groups on the green body surface Increase to facilitate glazing and produce glassy film.
[0021] In summary, the present invention provides a method for processing high-strength ceramic insulators, which has the following beneficial effects:
[0022] (I) In the technical solution of the present invention, diatomite and silicon powder are added to the blank, wherein diatomite has excellent thermal insulation properties, and the addition of diatomite can improve the thermal properties of ceramics. Silicon powder, as an additive in the blank, has excellent thermal and mechanical properties. At the same time, silicon powder particles can be filled to reduce the porosity of diatomite, further improving the strength of the insulator. In addition, the present invention can generate a glass-like state by ozone treatment on the surface of the blank during the glazing process. Thin films and more hydrophilic groups To facilitate glazing and improve the bonding strength between the glaze and the body.
[0023] (ii) In the technical scheme of the present invention, the soluble impurities in the diatomaceous earth in the glaze are removed by utilizing the weak acidity of boric acid, and the thermal decomposition reaction of boric acid is used to generate boron oxide residues while drying at high temperature after the impurities are removed. The boron oxide residues can react with the aluminum oxide in the glaze to generate aluminum borate whiskers during the firing process after the body is glazed. Aluminum borate has good mechanical strength, heat resistance, chemical resistance, acid resistance, electrical insulation, etc. Aluminum borate whiskers can be used as a reinforcing agent in the firing process of insulators to further improve the strength of the insulators.
[0024] Other features and advantages of the present invention will be set forth in the description which follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a flowchart of a method for processing a high-strength ceramic insulator. DETAILED DESCRIPTION
[0026] An embodiment of the present invention provides a method for processing a high-strength ceramic insulator. The embodiment of the present invention will be described in detail below with reference to the accompanying drawings.
[0027] Figure 1 Flow chart of a method for processing a high-strength ceramic insulator according to the present invention, as shown in FIG. Figure 1 As shown, a high-strength ceramic insulator processing method according to an embodiment of the present invention specifically includes the following steps:
[0028] S1-1, the following mass percentages of blank raw materials are used: kaolin ,diatomite , potassium feldspar , bentonite , Quartzite , Silicon powder ; It should be noted that, as a raw material for the blank, diatomaceous earth has excellent thermal insulation properties. Adding diatomaceous earth can improve the thermal properties of ceramics. Silicon powder, as an additive in the blank, has excellent thermal and mechanical properties, which can improve the performance of ceramics and reduce the porosity of the ceramic blank.
[0029] S1-2, the raw materials of the blank obtained in step S1-1 are sand-milled and sieved with a 200-mesh sieve respectively, and after mixing, they are wet-milled, granulated, aged, and pressed into shape, and dried to obtain a blank; mainly by drying at room temperature or low temperature, and the moisture content of the blank after drying is less than ;
[0030] S2-1, using the following mass percentage of glaze raw materials, diatomaceous earth , pyrophyllite , Kaolin ,talc , Borax , Quartzite It should be noted that, as a glaze raw material, pyrophyllite has a small and linear expansion coefficient, good thermal stability and very small wet expansion, which can improve the stability of the glaze;
[0031] S2-2, grinding the diatomite obtained in step S2-1 through a 120-mesh sieve, and grinding the other glaze raw materials through a 550-mesh sieve respectively, so that the other glaze raw materials can fill the surface mesopores of the diatomite;
[0032] S2-3, adding a saturated boric acid solution to the diatomaceous earth obtained in step S2-2 to obtain a mixed liquid, wherein the volume ratio of the diatomaceous earth to the saturated boric acid solution is , heating the mixed liquid to acid-leach the diatomite to obtain an intermediate liquid;
[0033] S2-4, filtering the intermediate liquid obtained in step S2-3 and heating it to obtain a dry solid;
[0034] S2-5, the dry solid obtained in step S2-4 is sand-milled again through a 120-mesh sieve, and mixed with other glaze raw materials obtained in step S2-2 to obtain a mixed glaze, and calcined until the specific gravity of the mixed glaze raw material is ;
[0035] S2-6, removing iron from the mixed glaze obtained in step S2-5 and then wet-milling it to obtain a glaze slurry;
[0036] S3-1, glazing the body obtained in step 1-2 and firing it to obtain a finished product, and ozone treatment is performed on the surface of the body during glazing.
[0037] Specifically, in this embodiment, during step S2-3, the acid leaching process is to heat to , insulation In conventional acid leaching and purification of diatomite, hydrofluoric acid and sulfuric acid are used to dissolve impurities in the diatomite. In this embodiment, saturated boric acid solution is used to purify the diatomite. The weak acidity of boric acid is used to dissolve only some impurities that are easily soluble in weak acid. Inorganic salts such as diatomite have low solubility in a weakly acidic environment and are therefore mostly retained. At the same time, acid leaching can increase the pore volume and specific surface area of diatomite and improve its pore structure while removing impurities from the diatomite, which is beneficial to particle filling in the subsequent mixed calcination process.
[0038] Specifically, in this embodiment, in step S2-4, the heating process is to heat to , insulation After filtering the intermediate liquid after acid leaching, it is heated and dried, and the remaining saturated boric acid solution is Thermal decomposition occurs at room temperature to generate boron oxide, water and oxygen. After further removal of water and oxygen, boron oxide remains.
[0039] Specifically, in this embodiment, during step S2-5, the calcination temperature is Calcination time is , and stirring during calcination, temperature can affect the mesoporous volume of diatomite, and diatomite The mesopore volume approaches the maximum value when , by The glaze is mixed and stirred under the environment, so that the glaze particles can fully fill the mesopores of the diatomite. At the same time, as the mixing proceeds and the mesopores of the diatomite are continuously filled, the specific gravity of the glaze raw materials gradually increases until the specific gravity of the mixed glaze raw materials is .
[0040] Specifically, in this embodiment, in step S3-1, the sintering process of the green body is as follows: The firing time is , ozone treatment time is , through ozone Treating the surface of the green body and making it hydrophilic can make the surface of the green body produce more The hydrophilic group is beneficial to the subsequent glazing and improves the bonding strength between the glaze and the body. At the same time, due to the addition of silicon powder in the body raw materials, the ozone treatment can produce silicon dioxide-based surface The film further facilitates the bonding of the glaze.
[0041] Specifically, in the present embodiment, during the firing process of the green body, the boron oxide remaining in step S2-4 reacts with the aluminum oxide contained in the glaze raw material to form aluminum borate whiskers. Aluminum borate has good mechanical strength, heat resistance, chemical resistance, acid resistance, electrical insulation, neutron absorption performance, and covalency with metals. Aluminum borate whiskers can be further used as a reinforcing agent during the firing process of the insulator to further improve the strength of the insulator.
[0042] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core ideas of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for processing a high-strength ceramic insulator, characterized in that: The specific steps include: S1-1, use the following mass percentage of blank raw materials, kaolin ,diatomite , potassium feldspar , bentonite , Quartzite , Silicon powder ; S1-2, the raw materials of the blank obtained in step S1-1 are sand-milled and sieved through a 200-mesh sieve respectively, and after mixing, they are wet-milled, granulated, aged, and pressed into shape, and dried to obtain a blank; S2-1, using the following mass percentage of glaze raw materials, diatomaceous earth , pyrophyllite , Kaolin ,talc , Borax , Quartzite ; S2-2, the diatomaceous earth obtained in step S2-1 is sand-ground through a 120-mesh sieve, and the other glaze raw materials are sand-ground through a 550-mesh sieve respectively; S2-3, adding a saturated boric acid solution to the diatomaceous earth obtained in step S2-2 to obtain a mixed liquid, wherein the volume ratio of the diatomaceous earth to the saturated boric acid solution is , heating the mixed liquid to acid-leach the diatomite to obtain an intermediate liquid; S2-4, filtering the intermediate liquid obtained in step S2-3 and heating it to obtain a dry solid; S2-5, the dry solid obtained in step S2-4 is sand-milled again through a 120-mesh sieve, and mixed with other glaze raw materials obtained in step S2-2 to obtain a mixed glaze, and calcined until the specific gravity of the mixed glaze raw material is ; S2-6, removing iron from the mixed glaze obtained in step S2-5 and then wet-milling it to obtain a glaze slurry; S3-1, glazing the body obtained in step 1-2 and firing it to obtain a finished product, wherein the surface of the body is subjected to ozone treatment during glazing.
2. A method for processing a high-strength ceramic insulator according to claim 1, characterized in that: In step S2-3, the acid leaching process is to heat to , insulation .
3. A method for processing a high-strength ceramic insulator according to claim 1, characterized in that: In the step S2-4, the heating process is to heat the temperature to , insulation .
4. A method for processing a high-strength ceramic insulator according to claim 1, characterized in that: In the step S2-5, the calcination temperature is Calcination time is , and stir during calcination.
5. The method for processing a high-strength ceramic insulator according to claim 1, characterized in that: In step S3-1, the sintering process of the green body is as follows: The firing time is , the ozone treatment time is .
Citation Information
Patent Citations
Preparation method of high-strength aluminum oxide suspension insulator and porcelain insulator structure
CN113968726A
Porcelain insulator slip casting method
CN114507063A
Preparation method of high-strength alumina-based porcelain insulator
CN118047596A